2002
DOI: 10.1289/ehp.02110939
|View full text |Cite
|
Sign up to set email alerts
|

Home and allergic characteristics of children with asthma in seven U.S. urban communities and design of an environmental intervention: the Inner-City Asthma Study.

Abstract: Most published environmental remediation interventions have been directed at single allergens and have employed demanding strategies; few have been performed in the homes of inner-city children disproportionately burdened by asthma. Our objective was a) to describe the allergen sensitivities, environmental tobacco smoke (ETS) exposure, and home environmental characteristics of a national sample of inner-city children with moderate to severe asthma and b) to develop and implement a multifaceted, home-based comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
125
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(129 citation statements)
references
References 34 publications
3
125
1
Order By: Relevance
“…Indeed, medication changes or optimization, such as targeted addition of antihistamines, allergen-specific immunotherapy (23, 24), or omalizumab; or referrals for in-home exposure assessment and remediation have the potential to reduce future exacerbations and improve asthma control (25)(26)(27). Initiation of in-home assessments may be particularly relevant given that reported exposures often differ from what is truly found in the home (21). The inpatient population could be an apt starting point for initiation of such assessments and interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, medication changes or optimization, such as targeted addition of antihistamines, allergen-specific immunotherapy (23, 24), or omalizumab; or referrals for in-home exposure assessment and remediation have the potential to reduce future exacerbations and improve asthma control (25)(26)(27). Initiation of in-home assessments may be particularly relevant given that reported exposures often differ from what is truly found in the home (21). The inpatient population could be an apt starting point for initiation of such assessments and interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Skin prick testing for 14 common indoor and outdoor allergens, completed as part of the National Cooperative Inner-City Asthma Study with children aged 4-9 years recruited from emergency departments and inner-city clinics, demonstrated that 77% had at least one positive skin test and 47% had at least three (20). Others have shown that 45% of inner-city children with moderate to severe asthma are exposed to mold and 50% to cockroaches (15,21). Routine allergy testing (22), medication changes or addition of allergen-specific immunotherapy (23,24), and public health interventions to assess in-home allergen exposure and reduce or remediate exposures that are found all have the potential to reduce asthma morbidity among high-risk patients (25)(26)(27).…”
mentioning
confidence: 99%
“…2 The reasons for this disparity are complex and include unhealthy home environ-ments. [3][4][5] Home environmental surveys in the inner city have documented that homes are frequently old and in poor repair, with leaky roofs, water damage, and mold contamination. In addition, cigarette smoking rates are high, cockroach and rodent infestation is common, 3,[5][6][7][8] and indoor NO 2 and particulate levels have been reported to be high.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Home environmental surveys in the inner city have documented that homes are frequently old and in poor repair, with leaky roofs, water damage, and mold contamination. In addition, cigarette smoking rates are high, cockroach and rodent infestation is common, 3,[5][6][7][8] and indoor NO 2 and particulate levels have been reported to be high. 3,9 All of these factors, especially indoor dampness and mold, airborne particulates, and indoor allergens, have been shown to be associated with increased morbidity among children with asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Studies from the United States indicated that asthmatic children from low-income families often are sensitized to multiple allergens to which they are frequently exposed (Crain et al, 2002;Perry et al, 2006), including cockroaches, dust mites, and molds (Gruchalla et al, 2005). Although information on skin testing was not available for the present study, the total number of triggers that were reported as worsening asthma was not significantly associated with the number of poor practices.…”
Section: Discussionmentioning
confidence: 62%